Clinical traits impacting human tissue transcriptomes - Kaur Alasoo (Elsevier, 2023)
In this issue of Cell Genomics, Garcia-Perez et al.1 report a comprehensive and careful association analysis between gene expression and splicing measured by the GTEx Consortium2 in 46 human tissues and 21 demographic and clinical traits.